Theoretical studies of iminoacetonitrile formation - Sandström, Hilda; Rahm, Martin (Chalmers University of Technology, 2021)
The purpose of this study is to investigate the dimerisation of HCN in the condensed phase. The included data consists of quantum chemical calculations and optimized structures involved in base-catalysed iminoacetonitrile formation. The dataset includes outputs from calculations done in Gaussian16, molecular dynamics simulations performed in CP2K v6.1, and calculations performed with the Vienna ab initio simulation package (v 5.4.4). The quantum chemical calculations are used to construct the energy profile of the iminoacetonitrile formation, providing information on the reaction kinetics and thermodynamics.

Syftet med studien är att konstruera en energiprofil för HCN dimerisering för att beräkna reaktionens kinetik och termodynamik. Datasetet består av molekylära strukturer inblandade i HCN dimerisering och output av kvantkemiska beräkningar av energin av de inblandade molekylerna.
Teoretisk studie kring bildning av iminoacetonitril
Keywords: Iminoacetonitrile; Iminoacetonitril; Metadynamics; Metadynamik; Hydrogen cyanide; vätecyanid; Theoretical Chemistry; Teoretisk kemi